Respuesta :
Answer:
An equation that would satisfy this is f(x) = x^2 - 11x + 2
Step-by-step explanation:
We know this because any equation with a 2 constant at the end will satisfy this. That's because when we input 0 in for a quadratic, the variable terms will equal 0, leaving only the constant.
Equation of a quadratic function will be f(x) = x² + 2x + 2.
Quadratic function is defined by the equation,
- f(x) = ax² + bx + c
Here, 'c' is the constant term.
If we substitute x = 0,
f(0) = a(0) + b(0) + c
f(0) = c
That means, any quadratic function having constant term as 2 will produce the result f(0) = 2
Therefore, equation of the quadratic function may be f(x) = x² + 2x + 2
Learn more,
https://brainly.com/question/3404535